Synthese und Kristallstruktur von Pentakis(dimethylsulfoxid)- oxo-titan(IV)chlorid: Herrn Professor Dr. Walter Siebert zum 60. Geburtstag gewidmet = Synthesis and crystal structure of Pentakis(dimethylsulfoxide)-oxo-titanium(IV) chloride - Enders, Markus; Rudolph, Ralph; Pritzkow, Hans (Zeitschrift für Naturforschung. B, a journal of chemical sciences, 1997)
Pentakis(dimethylsulfoxide)-oxo-titanium(IV) chloride is obtained by reaction of titanium tetrachloride with a stoichiometric amount of water in dimethylsulfoxide. A single crystal structure determination (P1̄, a = 9.564(6), b = 10.504(7), c = 12.510(8) Å, α = 70.21(5), β = 83.48(5), γ = 89.82(5)°, V = 1174 Å3, Z = 2) shows a dicationic titanium(IV) complex with five dimethylsulfoxide ligands and one oxygen atom. The two chlorine anions are not bonded to the complex cation. The TiO6-fragment is a distorted octahedron, where five of the six oxygen atoms belong to the coordinated dimethylsulfoxide molecules.